Artificial intelligence systems’ importance in the analysis of crimes and their patterns - AlAbdouli, Shaikha; Alomosh, Ahmad; BouNassif, Ali; Nasir, Qassim (Al-Adab Journal, 2023)
This study aims to identify the available artificial intelligence techniques, how to connect them to criminology, and how to use them in order to benefit from them in order to analyze crimes, discover their patterns, and take advantage of algorithms that help reduce crimes. This is to determine the importance of artificial intelligence systems in analyzing crimes and their patterns. In addition to the most popular data science languages, artificial intelligence algorithms, data gathering and analysis techniques, data mining mechanisms, and criminal patterns, the study revealed numerous concepts underlying artificial intelligence systems. The study’s findings include the following: using artificial intelligence in crime analysis shortens the time required for the analysis process; machine learning helps track crime and hotspots; and the most significant barrier to using artificial intelligence in Arab crime analysis is the dearth of qualified human resources. the lack of ongoing improvement, the absence of a precise and organized mechanism for gathering crime statistics, and the scarcity of data. One of the study’s most crucial recommendations is to focus on academic specializations in data science, gather the most data possible to increase the effectiveness of the analysis, and set up an Arab police association to regularly exchange experiences and knowledge, particularly between the Gulf Cooperation Council countries.